OHP-016 Consumption of Opioid Analgesics in Hospital Pharmacy and Consultative Care For Patients. (12th March 2013) - Sumberova, J; Lzicar, M; Kolar, J
Abstract : Background: In recent years the incidence of different types of pain is increasing. We have found the same in the St. Anne's hospital in the Czech Republic. Patients are now able to ask about the correct usage of opioid drugs in pharmacy consultation centre, which opened in 2011. Purpose: To find out the consumption of opioid analgesics from 2008 to 2011. This is an analysis of prescriptions by doctors from the pain treatment centre. We also collected data from patient records in the pharmacy consultation centre and we wanted to know how many patients come to consult us. Materials and Methods: Data were obtained from the pharmacy computer software. We made a retrospective evaluation, calculated the defined daily dosage (DDD) and compared consumption of opioid analgesics during 2008–2011 for ATC class N02A and other subclasses. We analysed the consultation records. Results: Consumption of weak opioids decreased over that time, while consumption of strong opioids increased, which had to be prescribed. Opiates were prescribed more often to women. The highest consumption was of buprenorphine, than fentanyl and oxycodone, from weak opioids it was tramadol. Consumption of fentanyl increased from 35 735 DDD (2010) to 39 924 DDD (2011), while buprenorphine consumption decreased from 45 059 DDD (2010) to 38 675 DDD (2011). The amount of morphine used last year was twice that of previous years. The total number of patients who visited the pharmacy consulting centre was 41, six patients were from the pain treatment centre. Average age was 61.3. Patients wanted to control interactions, secondly combat adverse effects of opioids and requested information about neuropathic pain. Average consultation length was 22.5 minutes. Conclusions: The consumption of strong opioids is gradually increasing, doctors follow guidelines and they aren't afraid of prescribing strong opioids. In future it would be appropriate to extend the distribution of informatory materials by the consultation centre – not only about the opioid analgesics. No conflict of interest.